Significance of Environmental Concepts in the Science Curriculum of Secondary Education in Sri Lanka - Mathura, U.; Piratheeban, K. (Faculty of Humanities and Sciences, SLIIT, 2023)
Environmental threats are serious concerns in the present world. Therefore, to reduce environmental threats, an environmental literate generation with positive attitudes and behaviours towards the environment should be created. In this manner, environmental education was introduced globally as a tool to create an eco-friendly generation. In Sri Lanka, environmental education was not introduced as a separate subject but rather as an integrated concept within the Science curriculum. Since, it is doubtful whether the existing curriculum satisfies the scope of environmental education, this qualitative study on content analysis is designed to examine the extent to which environmental concepts are emphasized compared with other science concepts in the secondary level science curriculum of Sri Lanka. Additionally, it aims to evaluate the extent to which the existing curriculum is expected to bring attitudinal changes related to the environmental. Secondary sources such as school textbook from grade six to eleven, teachers’ instructional manual and other relevant written documents of the government and various researchers were analyzed for this study. It is proved that less importance is placed to direct environmental concepts rather than other concepts in the curriculum. Accordingly, the number of instructional periods allocated for environmental-related units in the school text books are relatively low (Grade 6,7,8,9,10,11 : 11.2%, 15.4%, 0, 8.3%, 0 and 13.4% respectively). Furthermore, most of the learning outcomes that the students are expected to achieve focus on the development of knowledge dimension of environmental concepts rather than fostering eco-friendly attitudes. Therefore, there is a need to pace greater emphasis on environmental concepts in a manner that promotes attitudinal changes in students, which can ultimately result in the development of an eco-friendly generation.
Keywords: Environment; Environmental attitude; Secondary level curriculum; Science-curriculum